2018
DOI: 10.1002/aelm.201800055
|View full text |Cite
|
Sign up to set email alerts
|

Direct Demonstration of the Emergent Magnetism Resulting from the Multivalence Mn in a LaMnO3 Epitaxial Thin Film System

Abstract: Atomically engineered oxide heterostructures provide a fertile ground for creating novel states. For example, a two-dimensional electron gas at the interface between two oxide insulators, giant thermoelectric Seebeck coefficient, emergent ferromagnetism from otherwise nonmagnetic components, and colossal ionic conductivity. Extensive research efforts reveal that oxygen deficiency or lattice strain play an important role in determining these unexpected properties. Herein, by studying the abrupt presence of robu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 59 publications
6
28
0
Order By: Relevance
“…Compared to previous reports of diluting the LAO layer with nonpolar STO, this new approach provides an opportunity to tune the carrier density of the interfacial 2DEL without changing the polar discontinuity across the interface (Figure S2a, Supporting Information). Moreover, thick LaMnO 3 films are often ferromagnetic when epitaxially grown on STO . Therefore, this approach can also be used to study the magnetic proximity effect at LAO/STO interfaces as reported in EuTiO 3 ‐buffered LAO/STO …”
mentioning
confidence: 99%
“…Compared to previous reports of diluting the LAO layer with nonpolar STO, this new approach provides an opportunity to tune the carrier density of the interfacial 2DEL without changing the polar discontinuity across the interface (Figure S2a, Supporting Information). Moreover, thick LaMnO 3 films are often ferromagnetic when epitaxially grown on STO . Therefore, this approach can also be used to study the magnetic proximity effect at LAO/STO interfaces as reported in EuTiO 3 ‐buffered LAO/STO …”
mentioning
confidence: 99%
“…However, these spin‐polarized electrons have been detected often in the high carrier density range where both the d xy and d xz /d yz electrons are populated . Based on the ferromagnetism of LMO thin films on the STO, Gan et al later detected the anomalous Hall effect in oxide interfaces of LaAl 0.7 Mn 0.3 O 3 /STO where only the d xy band are populated …”
Section: Magnetic Fieldmentioning
confidence: 99%
“…One example for the second case is the LaMnO 3 /SrTiO 3 interface, of which the real spatial distribution of the magnetization is imaged as shown in Figure e . At this LaMnO 3 /SrTiO 3 interface, critical thickness modulation and multivalence Mn ions have also been investigated. After the charge transfer, the coexistence of Mn 2+ and Mn 3+ is observed at the interface with no indication of Mn 4+ at the surface .…”
Section: Emergent Phenomena At Functional Oxide Interfacesmentioning
confidence: 99%